ABOUT THE SECURITY MODEL OF DUAL-CHANNEL DEVICES WITHOUT CHANNEL RESTARTС - Razghonov , S. А.; Chernikov , D. О.; Horulia, М. М. (Systems and Technologies, 2026)
The majority of technical devices in transport have their own heating control. The article examines the power supply for the functional safety of dual-channel transport devices of robotic on-board systems. Current research into the safety and reliability of dual-channel monitoring devices has not been given sufficient respect. Thus, in other regulatory documents, for reliability, a comprehensive indicator of reliability (readiness coefficient of the device) is indicated by the appearance of average focus on vidmova to the sum of average focus on At the end of the day, at the middle hour of renewal. The values of the availability coefficient are determined for the purposes of operation of dual-channel devices if the average parameter for the flow of outputs and the average cost of renewal are deprived of steel. Such an interpretation conveys that any kind of device is revealed and then immediately updated, so that the control methods are ideal. It is difficult for real minds to create control mechanisms to provide a further guarantee of the identification of your identity. This article examines an approach that formalizes applied problems of functional security and allows one to find optimal solutions to applied problems. The safety and reliability of dual-channel control devices have been studied for many years now. The formulaic expressions of stationary and international networks have been removed for updating dual-channel devices with the required hardware control. These formulas allow us to establish real characteristics of the effectiveness and reliability of control methods, which promotes the reliability of the results of system analysis. It is clear that the reliability of the transport device lies in the power to preserve efficiency at a given time by preserving the performance characteristics of the relevant technical minds of the operation. This power is closely related to economical operating parameters. In the end pouch, economical parameters, in current minds, play a vital role in both the manufacturing system and business processes of operation. Take a brief look at the hourly demonstrations of the safety and reliability of the dual-channel controlled transport device of robotic on-board systems. What is important is the display of triviality between the vids and around the visiting vids, as well as the time of renewal and the time of the simple structure